Three‐Dimensional Reconstruction of Neovasculature in Solid Tumors and Basement Membrane Matrix Using Ex Vivo X‐ray Microcomputed Tomography. (February 2014) - Lee, Seunghyung; Barbe, Mary F.; Scalia, Rosario; Goldfinger, Lawrence E.
Abstract Objective To create accurate, high‐resolution 3D reconstructions of neovasculature structures in xenografted tumors and Matrigel plugs for quantitative analyses in angiogenesis studies in animal models. Methods The competent neovasculature within xenografted solid tumors or Matrigel plugs in mice was perfused with Microfil, a radioopaque, hydrophilic polymerizing contrast agent, by systemic perfusion of the blood circulation via the heart. The perfused tumors and plugs were resected and scanned by X‐ray micro‐CT to generate stacks of 2D images showing the radioopaque material. A nonbiased, precise postprocessing scheme was employed to eliminate background X‐ray absorbance from the extravascular tissue. The revised binary image stacks were compiled to reveal the Microfil‐casted neovasculature as 3D reconstructions. Vascular structural parameters were calculated from the refined 3D reconstructions using the scanner software. Results Clarified 3D reconstructions were sufficiently precise to allow measurements of vascular architecture to a diametric limit of resolution of 3 μm in tumors and plugs. Conclusions Ex vivo micro‐CT can be used for 3D reconstruction and quantitative analysis of neovasculature including microcirculation in solid tumors and Matrigel plugs. This method can be generally applied for reconstructing and measuring vascular structures in three dimensions.